TIME-REVERSAL INVARIANCE IN NUCLEAR GAMMA-DECAY - Rikovska, J; Griffiths, A; Stone, N; Ohya, S; Ashworth, C (Kluwer Academic Publishers, 1988)
Test experiments to study of T-and PT-reversal symmetry in nuclear γ-decay, using linear polarization of γ-rays from nuclei oriented by hyperfine interaction at low temperatures are discussed. The necessary formalism is reviewed and details of new proposals for future experiments are given. © 1998 J.C. Baltzer A.G., Scientific Publishing Company.